Pochwała filologii - Awierincew, Siergiej; Skalińska, Ewangelina (Colloquia Litteraria, 2014)
The Apology of Philology The paper deals with the basic goals of philology, which for the author is, first of all ”the science of understanding.” The traditional, perennial values of philology as a discipline are concentrated upon and they are analysed in contrast to sciences.